Physicochemical Properties of Surface Water, Heavy Metals Levels in Sediments and Macrobenthic Invertebrates Community of Ikpoba River, Benin City, Edo State, Nigeria - (:unkn) unknown (Journal of Applied Sciences and Environmental Management, 2026)
The objective of this paper was to investigate the physicochemical properties of surface water, heavy metals levels in sediments and macrobenthic invertebrate community of the Ikpoba River, Benin City, Edo State, Nigeria using appropriate standard methods. Data obtained show that the pH in the surface water ranged between 4.30 and 8.90 with a mean of 5.23. There was no significant difference (p > 0.05) in the physicochemical properties of surface water across the three stations. The mean values of heavy metals for iron, zinc, copper, lead and cadmium in sediments ranged from 22.30 - 45.30, 8.46 - 27.10, 1.80 - 12.40, 0.01 - 4.75 and 0.00 - 1.15 mg/l with a mean of 32.71±2, 17.62±1, 7.24±1, 1.29±01 and 0.17±0.1 mg/l respectively. However, metals such as iron, zinc, copper and lead were above the recommended limit for freshwater ecosystems. A total of 482 individual macrobenthic organisms were recorded in the study. The benthic organisms were dominated by the orders Ephemeroptera (23.03%), Diptera (22.61%), Hemiptera (18.26%) and Odonata (17.01%) with Baetis sp (6.02%), Velia sp (5.60%), Heptagenia sp (5.39%) and Lestes sp (4.36%) as the major representative species. For the biological indices, station 1 had the highest diversity, species richness and evenness. Station 3 had the lowest diversity and richness while the lowest species evenness was recorded in station 2. A weak correlation between the physicochemical parameters and the macroinvertebrate fauna was recorded. The calculated EPT Index for the macrobenthic fauna was 31.67 % indicating a fairly polluted river.
Keywords: ecological indicators; pollution studies; biogeochemistry; benthic invertebrates; water quality; EPT Index